The Effect of Financial Performance and Innovation on Leverage - Vania Calista; Ickhsanto Wahyudi (El-Qish: Journal of Islamic Economics, 2024)
This study aims to analyze the effect of asset structure, profitability, innovation, and technology on leverage in companies listed on the LQ45 index of the Indonesia Stock Exchange (IDX) during 2021–2023. The analysis is grounded in the Trade-Off Theory, which states that companies balance the tax benefits of debt with the risk of bankruptcy. A quantitative method with a causal approach was applied, utilizing secondary data from financial statements. Data were analyzed using multiple linear regression with SPSS, through classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation) and hypothesis testing (t-test, F-test, and coefficient of determination). The findings show that asset structure has a positive and significant effect on leverage, indicating that firms with more tangible assets tend to increase debt. Profitability also shows a significant effect, yet contrary to the initial hypothesis predicting a negative impact, the relationship was positive, suggesting profitable firms use debt to support growth. Innovation and technology had a negative but insignificant effect, implying limited influence on leverage decisions. Simultaneously, the three independent variables explained 79.3% of leverage variation as reflected by the Adjusted R Square, while the remaining 20.7% was affected by other factors not included in the research model.